Bleeding risk with concomitant use of tirofiban and third-generation P2Y(12) receptor antagonists in patients with acute myocardial infarction: A real-life data - (:unkn) unknown (AVES, 2021)
Objective: Combination of dual antiplatelet therapy (DAPT) with glycoprotein (GP) IIb/IIIa inhibitors can increase bleeding risk. In this study, we aimed to investigate bleeding complications of different DAPTs with concomitant tirofiban use in patients with acute coronary syndrome (ACS). Methods: This retrospective study included 224 consecutive ACS patients (mean age 56.6 +/- 11.1 years, 193 men) who were given conventional dose of tirofiban (25 mu g/kg per 3 minutes followed by an infusion of 0.15 mu g/kg/min for 24 hours) in addition to DAPT (300 mg aspirin followed by 100 mg/day + 600 mg clopidogrel followed by 75 mg/day or 180 mg ticagrelor followed by 90 mg twice daily or 60 mg prasugrel followed by 10 mg/day). Any intra-hospital bleeding complications were noted. Results: Of the 224 patients, 115 were given ticagrelor and 32 were given prasugrel. Mean hemoglobin fall was similar between the patients taking ticagrelor/prasugrel and those taking clopidogrel. Ten patients taking ticagrelor and one patient taking prasugrel had hemoglobin fall >= 3 g/dL versus two patients in clopidogrel group (p=0.228). Gastrointestinal bleeding (two patients taking ticagrelor), hematoma at access site (three patients taking ticagrelor), and cardiac tamponade (two patients taking ticagrelor) rates were also similar. Creatinine levels were associated with hemoglobin fall >= 3 g/dL (p=0.032, Odds ratio 2.189, 95% confidence interval 1.070-4.479). There was no relation between hemoglobin fall >= 3 g/dL and antiplatelet agent, age, sex, hypertension, or diabetes. Conclusion: Tirofiban may be given to patients receiving ticagrelor or prasugrel with a bleeding rate similar to clopidogrel. Close monitoring for bleeding risk is recommended, especially in patients with higher creatinine levels.
Keywords: acute coronary syndrome; bleeding; clopidogrel; prasugrel; ticagrelor; tirofiban; ACUTE CORONARY SYNDROMES; GLYCOPROTEIN IIB/IIIA INHIBITOR; PLATELET INHIBITION; ANTIPLATELET; EFFICACY; OUTCOMES; SAFETY; INTERVENTION; METAANALYSIS; CLOPIDOGREL